PREPARATION OF SCHOOL/MADRASAH ACCREDITATION FORMS IN IMPROVING EDUCATIONAL QUALITY - Rahmah; Habibah; Husnul Yaqin; Hilmi Mizani (PT. Hasba Edukasi Mandiri, 2026)
The preparation of school/madrasah accreditation forms is an important part of improving educational quality. Accreditation forms are not only used as administrative requirements, but also reflect the quality of school management. This study aims to describe the process of preparing accreditation forms, the role of educational management, the obstacles faced by schools, and the strategies that can be applied to improve the quality of accreditation form preparation. This research uses a library research method by reviewing various journals, books, and scientific sources related to school accreditation and educational management. The results show that the preparation process includes planning, data collection, instrument completion, verification, and document validation. In this process, educational management has an important role in organizing teamwork and managing school administration. In addition, several obstacles are still found in preparing accreditation forms, such as limited understanding of accreditation instruments, weak documentation systems, limited facilities and infrastructure, and time constraints. Therefore, strategies such as improving human resource competence, strengthening administrative systems, utilizing information technology, and increasing cooperation among school members are needed. Thus, the preparation of accreditation forms can become a means of evaluation and continuous improvement of educational quality.